Case report and literature review: Treatment of multiple meningiomas combined with multiple unruptured aneurysms in a single operation - Wei, Ren-jie; Wu, Xiao-lin; Xia, Feng; Chen, Jing-cao (Frontiers in Surgery, 2022)
Background Although the incidence of a single meningioma or single aneurysm is common, cases of multiple meningiomas combined with multiple aneurysms is rarely reported, and surgical treatment of the co-exist situation is also relatively uncommon. Case presentation A 38-year-old male patient presented to the neurosurgery department of our center with a headache. Examination revealed only symptoms of headache. Laboratory test showed only decreased total protein （TP）and albumin (ALB) .The magnetic resonance imaging (MRI) showed preoccupation of the frontal lobe and the right temple bone. Magnetic resonance angiography (MRA) and digital subtraction angiography (DSA) showed two aneurysms in the Anterior communicating artery (ACOA) and right anterior cerebral artery (ACA). Based on a combination of the patients’ history and image findings, we had the hypothesis that the patient was simultaneous suffering from meningioma and the aneurysm, and both of them are multiple. The patient underwent tumor resection and clipping procedure based on this hypothesis in one surgery. The intraoperative biopsy proved to be a meningioma. On the 10th postoperative day, the patient was discharged, and postoperative follow-up suggested no complications. Conclusion Multiple meningiomas combined with multiple aneurysms is rare to be reported in the same patient. For those unruptured intracranial aneurysms (UIAs) located in the visual field of craniotomy prepared for the brain tumor like meningioma, it’s possible to do the clipping as well. When the Meningiomas are multiple、 fitted with the surgical indication、and located in the position that can’t be treated in one surgery, that may lead to the two stage operation, no matter where the UIAs are located. Keywords: falx brain tumor, multiple meningiomas, multiple aneurysms，case report